2017
DOI: 10.1016/j.jwpe.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychrophilic temperature shocks on a gas-lift anaerobic membrane bioreactor (Gl-AnMBR) treating synthetic domestic wastewater

Abstract: 24Municipal wastewater is a renewable resource containing energy, nutrients and water. These 25 valuable constituents can be recovered via new, innovative technologies, such as the gas-lift 26 anaerobic membrane bioreactor (Gl-AnMBR), which is especially suitable for decentralized 27 wastewater treatment. To better understand the effects of fluctuating environmental conditions 28 on the treatment performance, the impact of short-term temperature shocks was studied. We 29 present a laboratory study of a 10 L Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…Despite the increase on VFAs in the effluent and the decrease on COD removal efficiencies, the reactor maintained its anaerobic activity and the production of biogas. This result contrasts with the study Dolejs et al (2017) in which a decrease of temperature from 34 to 15°C in an AnMBR treating synthetic municipal wastewater led to a complete inhibition of the biological processes after two weeks of operation at this temperature, confirmed by the absence of both biogas production and VFA accumulation.…”
Section: Performance At 15 °Ccontrasting
confidence: 99%
“…Despite the increase on VFAs in the effluent and the decrease on COD removal efficiencies, the reactor maintained its anaerobic activity and the production of biogas. This result contrasts with the study Dolejs et al (2017) in which a decrease of temperature from 34 to 15°C in an AnMBR treating synthetic municipal wastewater led to a complete inhibition of the biological processes after two weeks of operation at this temperature, confirmed by the absence of both biogas production and VFA accumulation.…”
Section: Performance At 15 °Ccontrasting
confidence: 99%
“…Thus, this signifies a reduction in suspended biomass activity. Dolejs et al [53] conducted a research on the effect of psychrophilic temperature shocks on a gas-lift anaerobic membrane bioreactor (Gl-AnMBR) used for treating synthetic domestic wastewater. The stability of the system was measured by transiting between mesophilic and psychrophilic stages having several psychrophilic shocks (12-48 h).…”
Section: Municipal Wastewatermentioning
confidence: 99%
“…Temperature fluctuations have an important effect on anaerobic degradation. Mesophilic bacteria are resistant to fluctuations of ±3 • C, but thermophiles are more sensitive and require longer adaptation to new conditions [22].…”
Section: Temperaturementioning
confidence: 99%
“…Other types include bioreactors, such as the gas-lift AnMBR, sponge AnMBR and sponge-granular AnMBR, as well as the AnMBR bioreactors used in research without their type being mentioned in the published articles. Dolejs et al investigated the effect of temperature shocks on the gas-lift AnMBR and reported that the gas-lift AnMBR was particularly suited to decentralized wastewater treatment [22]. The system efficiently operated (COD removal >80%) even after short-term decreases to 15 • C.…”
Section: Type Of Anaerobic Bioreactormentioning
confidence: 99%
See 1 more Smart Citation